Communautés en ligne et mesure de l’opinion - Romain Badouard (Communication)
This article looks at a certain method of conducting online surveys based on the principle of internet users, which is referred to as . Large numbers of potential customers of a given product or service are gathered together in a closed forum and to more or less freely talk about their practices. Through a field study, the author offers a new perspective on the relationships between Web professionals, their representations of the audiences they mobilize, and the effective practices of internet users.